LEGAL DISCOURSE OF DAGESTANI THEOLOGIANS OF THE 17TH-19TH CENTURIES (BASED ON THE MANUSCRIPT FROM THE BAGUZHALAV AL-MACHADI’S COLLECTION) - Abdulmazidov, Ramazan Sultanovic; Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper presents an analysis of a unique manuscript identified in the book collection of a prominent Dagestani theologian Baguzhalav al-Machadi. It comprises 9 works compiled in the form of questions and answers, which reflect the theological discourse on various legal aspects. The discussion was attended by such reputed theologians as Dawud al-Usishi, Sheikh Izz ad-Din Tayyib, Said al-Makki, Muhammad-haji al-Uradi, Muhammad al-Aliji, Sheikh as-Sijini, Hadith al-Machadi, Muhammad al-Hifnawi and Muhammad al-Aymaki. Some of them were Dagestanis, while others – of the Middle East origin. Their works are written in a form of answers of a number of Middle Eastern theologians to the questions of Dagestanis on various topical issues of that time. The works were compiled in the second half of the 17th – first quarter of the 19th centuries, which allows to trace to a certain extent the development of the legal tradition of Dagestan of that period. They are also a valuable source on the history of everyday life, economic and socio-political development of Dagestan society. The range of questions and answers considered in the theological discourse is extremely diverse, and concerns the various aspects of everyday life. As we believe, Dagestani theologians, turning to their more authoritative compatriots, as well as to scholars from the Middle East, sought to legitimize adat norms through Sharia texts. At the same time, addressing the latter, Dagestani theologians sought to use the unspoken priority in favor of their opinion that existed in the Muslim world. Moreover, the identified Arabic-language sources clearly demonstrate how closely Dagestan was included in the unified legal field of the Arab-Muslim world.
Keywords: Dagestan; Islamic law; adat; sharia; Arabic writings; Bagujalav al-Machadi